基于ObjectARX实现零件的特征建模 - 晁彩霞; 魏永乐 (Jixie chuandong)
Aiming at the shortage of the AutoCAD system in feature-modeling,the feature-modeling of part is realized on AutoCAD with the development tool of ObjcetARX and the technology of object-oriented.It has some advantages of friendly user interface,operating easily and high efficiency of design.The geometry and non-geometry information of feature can be inputted conveniently and provide more information for the following processes,so that the integration of CAD and the following CAPP/CAM is easily.The realization of the system indicates that developing the feature-modeling system using the entity-modeling function of the existing CAD system is a simple and effective method of realizing the integration of CAD/CAM.